Unveiling Firm Value: The Role of ESG, Cash Holding, and Retention Ratio with Firm Size as a Moderator - Anggie Nur Cahyani; Eny Maryanti; Sarwenda Biduri; Risha Tri Amanda (IECON: International Economics and Business Conference, 2025)
Firm value holds significant importance, as an increase in firm value reflects greater wealth and prosperity for shareholders. A higher stock price typically signifies a rise in firm value. This research investigates the influence of Environmental, Social, and Governance (ESG), cash holding, and retention ratio on firm value, with firm size serving as a moderating variable. The study employed a purposive sampling technique, focusing on manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2023 period, resulting in a total sample of 94 companies. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) through the SPSS 26 software. The findings reveal that both ESG and cash holding have a positive impact on firm value, while the retention ratio does not show a significant effect. Additionally, firm size moderates the relationship between ESG and retention ratio with firm value but does not moderate the relationship between cash holding and firm value.